Quantum confinement-induced semimetal-to-semiconductor evolution in large-area ultra-thin PtSe2 films grown at 400 °C - Ansari, Lida; Monaghan, Scott; McEvoy, Niall; Coileáin, Cormac Ó; Cullen, Conor P.; Lin, Jun; Siris, Rita; Stimpel-Lindner, Tanja; Burke, Kevin F.; Mirabelli, Gioele; Duffy, Ray; Caruso, Enrico; et al. (NPJ 2D materials and applications, 2019)
In this work, we present a comprehensive theoretical and experimental study of quantum confinement in layered platinum diselenide (PtSe 2 ) films as a function of film thickness. Our electrical measurements, in combination with density functional theory calculations, show distinct layer-dependent semimetal-to-semiconductor evolution in PtSe 2 films, and highlight the importance of including van der Waals interactions, Green’s function calibration, and screened Coulomb interactions in the determination of the thickness-dependent PtSe 2 energy gap. Large-area PtSe 2 films of varying thickness (2.5–6.5 nm) were formed at 400 °C by thermally assisted conversion of ultra-thin platinum films on Si/SiO 2 substrates. The PtSe 2 films exhibit p -type semiconducting behavior with hole mobility values up to 13 cm 2 /V·s. Metal-oxide-semiconductor field-effect transistors have been fabricated using the grown PtSe 2 films and a gate field-controlled switching performance with an I ON / I OFF ratio of >230 has been measured at room temperature for a 2.5–3 nm PtSe 2 film, while the ratio drops to <2 for 5–6.5 nm-thick PtSe 2 films, consistent with a semiconducting-to-semimetallic transition with increasing PtSe 2 film thickness. These experimental observations indicate that the low-temperature growth of semimetallic or semiconducting PtSe 2 could be integrated into the back-end-of-line of a silicon complementary metal-oxide-semiconductor process.